The Unity between Man and Homeland in Ali Oqla Orsan’s Sakhrat al-Joulaan Novel - Ali Bayanlou (دراسات فی اللغه العربیه و آدابها)
Sakhrat al-Joulaan authored by the Syrian writer, Orsan, attempts to convince the audience to accept the idea of the unity of humans and their homelands. To this end, Orsan applies literary figures to deepen the concept of unity. The abundance of literary images is a vivid feature of this novel, which includes monologues, free associations and stream of consciousness. The present paper investigates the relationship between human and homeland in the context of literary images. It employs a descriptive-analytic method and identifies the elements of the image and interprets them. The results show that the interactions between human and homeland are frequent through similes, metaphor, myths and symbols. The smiles and metaphorical elements sometimes appear in isolation or in a merged format and both of them complement each other. This feature is considered to be the author's style of presentation of mixed images. The author adds to the depth of thoughts by resorting to symbolic images embedded in the context of different concepts. Sometimes, the “cliff” in different interconnected context is symbolic or representative of homeland, objects and individuals. The word “cliff” is therefore, a signifier having various signified concepts and is a representative for fundamental symbolic images.